-1/5-4(m+1/12)=39/10(m-11/6)

Simple and best practice solution for -1/5-4(m+1/12)=39/10(m-11/6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -1/5-4(m+1/12)=39/10(m-11/6) equation:


-1/5-4(m+1/12)=39/10(m-11/6)

We simplify the equation to the form, which is simple to understand
-1/5-4(m+1/12)=39/10(m-11/6)

Simplifying:
-0.2-4*(m+1/12)=39/10*(m-11/6)

Simplifying:
-0.2-4*(m + 0.0833333333333)=39/10*(m-11/6)

Simplifying:
-0.2-4*(m + 0.0833333333333)=+3.9*(m-11/6)

Simplifying:
-0.2-4*(m + 0.0833333333333)=+3.9*(m-1.83333333333)

Reorder the terms in parentheses
-0.2+(-4m-0.333333333333)=+3.9*(m-1.83333333333)

Remove unnecessary parentheses
-0.2-4m-0.333333333333=+3.9+*(+m-1.83333333333+)

Reorder the terms in parentheses
-0.2-4m-0.333333333333=+(+3.9m-7.15)

Remove unnecessary parentheses
-0.2-4m-0.333333333333=+3.9m-7.15

We move all terms containing m to the left and all other terms to the right.
-4m-3.9m=-7.15 + 0.2 + 0.333333333333

We simplify left and right side of the equation.
-7.9m=-6.61666666667

We divide both sides of the equation by -7.9 to get m.
m=0.837552742616

See similar equations:

| a^2b^2-121=0 | | 9+-10x+x^4=0 | | x+6x-40=0 | | -10x+3+9x=-x-7 | | x^4-10x+9=0 | | 5v^3-65v^2+200v=0 | | 2x-7/3=-7 | | 8a+a= | | 6a+12=2a-6 | | 8a-3b+2a+6b= | | 3y+5y=9y | | m^2+9m+7=-5+9(-5)+7 | | 5x^2+10x=40 | | w^2+7w=8 | | 2w^2+6w=8 | | 4x^2=-9x-5 | | 3a^2+a+20=0 | | 3a^2+7a+20=0 | | 11-7-x=79-21x | | x^2=4x-21 | | w^2-14w+49= | | 15c^2+23c-28=0 | | 4x+15y=7000 | | 4x^2+8x-192=0 | | 12m+8=24 | | 15z^2-16z=-4 | | 32c^2-20c+24c-15=0 | | 2(3x+9)=7x+80 | | 5x^2+12x=-4 | | 2z^2-13z=-21 | | x^2+7x+13=1 | | 5x^2+37x=-14 |

Equations solver categories